Thematic analysis of issues experienced by blended learning learners / Noridah Abu Bakar … [et al.] - Abu Bakar, Noridah; Haji Arshad, Noor Habibah; Ramly, Saliza; Noradzan, Haslinda (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
Blended learning has been recognised as an opportunity to improve the teaching and learning process by complementing the strengths and weaknesses of face-to-face instructions and online learning. While most researches focused on the success factors, there is a research gap in the issues of blended learning which has become a barrier to the learning process. This research seeks to explore the issues of blended learning process experienced by learners in higher education. A survey to a selected group of Blended Learning learners based on convenience sampling techniques was carried out to explore these issues. Qualitative data analysis was used to analyse descriptive data thematically and categorised into few main themes. With regards to the issues, 37 raw themes were identified and were categorised into seven (7) main themes. The findings showed that Learning Management System (LMS) was the main issue followed by engagement issue, material issue, server issue, network issue, instructor issue and device issue. The recommendations made by the respondents were also discussed as their points of view are treasured. This study has direct implications to higher education policy makers, ICT administrative teams, curriculum designers, and educators as instructors for blended learning approach.